Electrodeposition of alloys or compounds in molten salts and applications - Taxil P.; Chamelot P.; Massot L.; Hamel C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This article deals with the different modes of preparation of alloys or intermetallic compounds using the electrodeposition in molten salts, more particularly molten alkali fluorides. The interest in this process is to obtain new materials for high technology, particularly the compounds of reactive components such as actinides, rare earth and refractory metals. Two ways of preparation are considered: (i) electrocoating of the more reactive metal on a cathode made of the noble one and reaction between the two metals in contact, and (ii) electrocoating on an inert cathode of the intermetallic compound by coreduction of the ions of each elements. The kinetic is controlled by the reaction at the electrolyte interface. A wide bibliographic survey on the preparation of various compounds (intermetallic compounds, borides, carbides…) is given and a special attention is paid to the own experience of the authors in the preparation of these compounds and interpretation of their results.